Environmental challenges and traditional food practices: The indigenous lundayeh of long pasia, sabah, borneo - Kavitha Ganesan; Anantha Raman Govindasamy; Jane Wong Kon Ling; Shaffarullah Abdul Rahman; Kennedy Aaron Aguol; Jamsari Hashim; Bilcher Bala (2020)
In this paper we focus on the Lundayeh indigenous minority in Long Pasia, Sabah by examining how their traditional food practices help them navigate environmental challenges. Deforestation and logging threaten the very core of the Lundayeh identity because the community’s livelihood as subsistence farmers depends on hunting as well as gathering forest resources. This paper argues that, despite the continuous challenges, Lundayeh food practices, albeit exercised in modified forms, provide an avenue to revisit past traditions in order for the community’s indigeneity and sovereignty to survive and be safeguarded. The findings of this research project suggest that through hunting techniques, foraging, paddy cultivation, agricultural cooperative work, as well as religiously sensitive food adaptation practices, the Lundayeh’s relationship with the land endures, which in turn, secures the community’s indigenous identity.